Effects of Glyphosate on Enzyme Activity and Serum Glucose in Rats Rattus norvegicus - Hasković Edhem (Sciendo, 2016)
Glyphosate is a pesticide that influences many blood parameters if taken orally or subcutaneously. This pesticide causes important changes in the metabolic activity which can be measured by organospecific enzyme activity such as liver aminotransferases (AST and ALT), while glucose acts as a stress, energy and metabolism indicator after acute glyphosate exposure. In this research, glyphosate was applied subcutaneously to rats, administrated each 24 hours for a 15 days period. The concentration of the applied glyphosate was 2.8 g/kg. The experimental rats were 13 weeks old. The concentration of serum glucose, the activity of lactate dehydrogenase and liver transaminases (AST and ALT) were observed as indicators of metabolic changes after treatment. It was observed that glyphosate led to a statistically significant decrease of serum glucose level. Statistically significantly increased (p<0.05) AST, ALT and LDH activities are indicators of hepatocyte damage while LDH activity demonstrates damage of other tissues.